Reactive Deposition Versus Strong Electrostatic Adsorption (SEA): A Key to Highly Active Single Atom Co-Catalysts in Photocatalytic H2 Generation - Wang, Yue; Qin, Shanshan; Denisov, Nikita; Kim, Hyesung; Bad'ura, Zdeněk; Sarma, Bidyut Bikash; Schmuki, Patrik (Advanced materials (Deerfield Beach, Fla.), 2023)
In recent years, the use of single atoms (SAs) has become of a rapidly increasing significance in photocatalytic H2 generation; here SA noble metals (mainly Pt SAs) can act as highly effective co-catalysts. The classic strategy to decorate oxide semiconductor surfaces with maximally dispersed SAs relies on "strong electrostatic adsorption" (SEA) of suitable noble metal complexes. In the case of TiO2 - the classic benchmark photocatalyst - SEA calls for adsorption of cationic Pt complexes such as [(NH3 )4 Pt]2+ which then are thermally reacted to surface-bound SAs. While SEA is widely used in literature, in the present work it is shown by a direct comparison that reactive attachment based on the reductive anchoring of SAs, e.g., from hexachloroplatinic(IV) acid (H2 PtCl6 ) leads directly to SAs in a configuration with a significantly higher specific activity than SAs deposited with SEA - and this at a significantly lower Pt loading and without any thermal post-deposition treatments. Overall, the work demonstrates that the reactive deposition strategy is superior to the classic SEA concept as it provides a direct electronically well-connected SA-anchoring and thus leads to highly active single-atom sites in photocatalysis.
Keywords: highly reactive single-atom deposition; photocatalytic H2 generations; Pt co-catalysts; sputtered anatase layers